Steel Structure Analysis of Workshop Facility in PT Pamapersada Nusantara - Mirza Abdul Halim; Dedy Rutama; Ribut Nawang Sari (Journal of Global Engineering Research and Science, 2022)
Structural planning in building construction aims to measure a building ability in bearing occurred loads. The structural elements must be designed and calculated based on the appropriate combination of standard loads. Workshop facility project at PT. Pamapersada Nusantara uses a steel structure with steel profiles for columns and beams. The function of the steel profile as a cross section of the structure is very important, for that it is necessary to analyze and design the right steel profile for the structural elements of steel columns and beams at the Workshop Facility Project of PT. Pamapersada Nusantara. The method used in this research is based on a case study on the object of research in the project. This building structure planning was analyzed using a computer-based structural calculation program, namely the SAP2000 v.14, referring to SNI 1729-2020 concerning Procedures for Planning Steel Structures for Buildings and SNI 1726:2019 Procedures for Planning Earthquake Resistance for Building Structures and Non-Building and SNI 1727:2020 Minimum Load for Design of Buildings and Other Structures and Indonesian Loading Regulations for Buildings (PPIUG 2019). The result of structure analysis using SAP2000 V.22, there were no failed frames in workshop facility structure making. For the Rafter deflection of 29.35 mm £ 31 mm (permitted deflection) and the column slenderness of 7 m (L) ³ (Lr) 5.74 m.